Constructing nonprofit-business collaboration: Bridging the divide - Wing, Kathryn (2013)
This research explores how individual nonprofit practitioners construct their complex identities and nuanced roles, as enablers of nonprofit-business collaboration, drawing on the discourse theory of “figured worlds” (Holland et al., 1998).